Order routing decisions for a fragmented market: A review - Suchismita Mishra; Le Zhao (Journal of Risk and Financial Management, 2021)
This paper reviews the up-to-date theoretical, empirical, and experimental literature related to the trading venue choice in the context of the fragmented equity markets. We provide a brief background on the history of trading fragmentation in the equity market and its determinants. We discuss the direct and indirect impacts of the market fragmentation on market quality in various dimensions, including liquidity, volatility, and price efficiency. Next, we identify possible determinants and channels from theoretical and empirical studies that could explain order routing decisions and present the possible directions for future research. Finally, we discuss the major regulatory reforms in the U.S. equity market on routing venue decisions. This topic is relevant in current times when phenomena such as 'GameStop Frenzy' have drawn significant attention to commission-free trading venues.
Keywords: 330; market structure; fragmentation; market quality; trading volume; order routing decision